Association between Memory and Attention Performance among Preschoolers Playing Traditional and Digital Games (on the Example of «Dobble») - O.V. Rubtsova; Y.A. Tokarchuk; O.V. Salomatova; E.V. Gavrilova (Moscow State University of Psychology and Education, 2024)
The article presents the results of the project «The Impact of Digital Activity on the Development of Cognitive Functions in Preschool Age». The study was conducted from February to May 2023 at the Center for Interdisciplinary Research of Contemporary Childhood at MSUPE, involving 76 children from preparatory groups of kindergartens in Moscow. The following methods were used: the «Learning 10 Words» Method (A.R. Luria), D. Weksler's Subtest (the «Coding Method»), 3.    «Test of Intertwined Lines» (A. Rey's Test Modification), and the «Mark the Signs» Method (Pieron-Ruser Test). According to the obtained data, the digital version of the game «Dobble» has the greatest effect on the development of the studied parameters of memory and attention in preschool children. The obtained empirical data are consistent with the results of similar studies and are of interest to psychologists, educators, and parents in planning and conducting educational and play activities.